2018
DOI: 10.1016/j.stueduc.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Promoting quality and equity: An exploratory case study of a primary school in England exploring barriers and facilitators in implementing the Dynamic Approach to school improvement

Abstract: A number of studies have been conducted to identify the impact of the Dynamic Approach to School Improvement (DASI) on student outcomes, using mainly quantitative and experimental designs. However, few studies explored the impact of DASI in schools facing challenging circumstances using qualitative methods. This in turn restricts our ability to provide in-depth and detailed explanations of how, why and under which conditions DASI works in improving student outcomes in socially disadvantaged schools. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…According to a number of studies, if teachers have a positive attitude towards their profession, they tend to complete teaching tasks more effectively (e.g. Gun, 2012; Onen and Ulusoy, 2012; Antoniou and Griaznova, 2018). Studies have also demonstrated that teachers' attitudes towards elements of their work are positively associated with teacher self-efficacy and teacher job satisfaction (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…According to a number of studies, if teachers have a positive attitude towards their profession, they tend to complete teaching tasks more effectively (e.g. Gun, 2012; Onen and Ulusoy, 2012; Antoniou and Griaznova, 2018). Studies have also demonstrated that teachers' attitudes towards elements of their work are positively associated with teacher self-efficacy and teacher job satisfaction (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The last two papers of this special issue, followed a different methodology for addressing the issue of equity. Charalambous et al (this issue), conducted an experimental study to search for the impact of a specific intervention at the school level on both quality and equity, whereas Antoniou and Griaznova (2017) used qualitative methods to investigate the effects of a school based intervention on students' outcomes in a specific primary school (an exploratory case study). Both studies have applied the dynamic approach to school improvement (DASI) (Creemers & Kyriakides, 2012) to schools situated in socially disadvantaged areas by highlighting the importance of conducting school improvement projects that are based on a theoretical framework that has been empirically tested (see Creemers & Kyriakides, 2015).…”
Section: Investigating the Quality And Equity Dimensions Of Effectiveness Through Different Methodological And Theoretical Approachesmentioning
confidence: 99%
“…The experimental schools of this study which made use of DASI have managed to achieve better student learning outcomes than the control schools (quality dimension) and the direct impact of SES on student achievement was reduced only in the experimental schools (equity dimension). Antoniou and Griaznova (2017), used semi-structured interviews to 16 teachers of a primary school in England to identify the facilitators and barriers of the DASI intervention. In this way, the authors of the paper gain a better understanding of the conditions under which school improvement initiatives prove to be effective in relation to student outcomes.…”
Section: Investigating the Quality And Equity Dimensions Of Effectiveness Through Different Methodological And Theoretical Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the constant comparative method was used to analyse data that emerged from interviews with the head teachers, school coordinators and teachers in each school. These interviews were concerned with the experiences and attitudes of school stakeholders towards the implementation of the intervention that took place in their schools (see Antoniou and Griaznova 2018). The analysis of the qualitative data helped us generate ordinal data measuring the extent to which each school in the experimental and control groups invested efforts into implementing their improvement strategies and action plans.…”
Section: Improvement Effortmentioning
confidence: 99%